Prescribed Burn Program Best Practices For Southern Michigan: From Indigenous Partnerships to Communication & Burn Plans ... - Baird, Allegra; McAtee, Anna; Salgado, Vincent; Woodruff, Foster (My University, 2023)
Prescribed burning is an important tool for managing diverse landscapes to meet site goals. For a land stewardship organization to establish or update a comprehensive burn program, they must respectfully acknowledge and incorporate the long and complex Indigenous history associated with fire, build successful partnerships and community engagement, and employ best available fire science in planning prescribed burns. Gathering and applying all of the relevant information, processes, and protocols can be a major challenge, especially for organizations with limited resources and capacity. Working together with the Southeast Michigan Land Conservancy (SMLC), we address these needs for a broader audience of southern Michigan land stewards. Specifically, we synthesized a variety of sources and perspectives to provide: 1) A deep understanding not just of fire history in Southern Michigan, but also of the culture, rights, knowledges, and histories of the Anishinaabeg in order to build respectful and informed fire ...